Ammonium monoethyloxalate (AmEtOx): a new agent for the conservation of carbonate stone substrates. (16th February 2021) - Aragoni, M. Carla; Giacopetti, Laura; Arca, Massimiliano; Carcangiu, Gianfranco; Columbu, Stefano; Gimeno, Domingo; Isaia, Francesco; Lippolis, Vito; Meloni, Paola; Ezquerra, Antonia Navarro; Podda, Enrico; Rius, Jordi; et al.
Abstract : Ammonium monoethyloxalate (AmEtOx) is proposed as a consolidanting agent for carbonate stones such as biomicritic limestone and marble, resulting in the formation of a microcrystalline passivating phase of calcium oxalate (whewellite and weddellite). Abstract : The ammonium salt of monoethyloxalate (AmEtOx) was investigated as a novel precursor for the conservation of carbonate stone substrates, such as biomicritic limestone and marble. Full characterization of treated and untreated authentic stone samples was carried out by means of SEM, X-ray powder diffraction, synchrotron tts-μXRD measurements, mercury intrusion porosimetry, determination of water transport properties, and pull-off tests. The improved solubility (1.49 M, 20.1% w/w) of AmEtOx as compared to that of ammonium oxalate (AmOx; 0.4 M, 5% w/w) results in the formation of microcrystalline phases 30–50 and 200–500 μm thick of calcium oxalate mono-(whewellite) or dihydrate (weddellite), on marble and biomicrite samples, respectively, after treatment with AmEtOx 5% and 12% w/w aqueous solutions. As a result, a reduction in the porosity of the stone samples and an enhancement of their cohesion are observed. DFT calculations, carried out to investigate the hydrolysis reaction leading from AmEtOx to AmOx, showed that the localization of the Lowest Unoccupied Molecular Orbital (LUMO) and the natural charge distribution account nicely for the tendency to hydrolyse observed experimentally, eventually leading to the formation of whewellite and weddellite on the stone surface.